(untitled) (Research, Society and Development, 2025)
Objective: The present literature review aimed to evaluate the different surgical techniques for vertical ridge augmentation in relation to the predictability of bone gain, the risk of complications, the success or failure rate of installed implants, as well as their survival rate. Methods: A narrative literature review was conducted, of a qualitative nature, with little systematization, in which data collection was carried out in the Scientific Electronic Library Online (SciELO) and the National Library of Medicine (PubMed) databases. Results: After analyzing the articles included in the review, the results of the studies showed that there are countless techniques able to produce a significant gain in thickness and height of the alveolar edge in jaws. Conclusion: despite the evolution of countless surgical techniques, the predictability of the vertical increase of the alveolar edge remains a challenge.